Pengaruh konseling obat terhadap pengetahuan dan tingkat kepatuhan pasien hipertensi Tahun 2023 - Nainggolan , Intan; Nurasni, Nurasni; Simanjuntak, Nerly Juli Pranita; Novriani , Erida; Piska , Finna; Meutia , Rena; Neswita, Elfia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Hypertension is when blood pressure exceeds normal limits, and it is generally a lifelong condition that requires maintaining stable blood pressure. Every year, the relationship between hypertension and death from heart and blood vessel disease stabilizes. Every year, the link between hypertension and death from heart and blood vessel disease is proven. This research took place from July to September 2023 at H. Adam Malik Hospital, Medan, with 53 patients who met the inclusion criteria. The study aims to assess the level of adherence of hypertensive patients to the use of their medication using the Morisky Medication Adherence Scale questionnaire and to see whether counseling can increase the level of patient compliance. The results of the analysis show that providing counseling has a significant impact on increasing compliance in hypertensive patients at H.Adam Malik General Hospital, Medan, as demonstrated by the Wilcoxon test with p-value < 0.05.